Proposed Knowledge Management Strategy by Leveraging Current Technology to Increase Productivity Operation in PT. Trimata Benua - Herdy Herdy; Jann Hidajat Tjakraatmaja (UniSadhuGuna Business School, 2023)
As coal industries is still attractive in the world, and a significant contributor for energy production which account approximately 37% for electricity generation. This type of fossil fuel is still being used by many countries despite it negative side effect to environment for example a greenhouse gas emission. Coal attractiveness is due to the fact that it is cheaper compared to other fossil fuel, resulting coal industries is still growing and predicted for many years to come. In Asia Pacific there are many countries dubbed as largest producers of coal, with China, India, and Indonesia being on the top three countries in Asia Pacific. With expected growth of 3.5% on yearly basis this makes Asia Pacific a significant contributor of the worlds coal industry. With that as well Asia Pacific contributes around 52% of the worlds carbon emissions in year 2020. Indonesia as the third largest coal producers, have approximately 8.9% growth in 2021. With projected coal production of 2.6% Year on Year. PT. Trimata Benua is one of the key players in Indonesia’s coal production. However, the company experience lack of productivity in operations, causing their production target missed. Is the absence of knowledge management system in the company causing that issue to arise. With that the company need to roll out and plan effective and structured knowledge management system to address their business issue. This research is based on three research questions. First one what is the best fit knowledge management strategy, second is to identify issues in operations, and the last one is to have suggestion for the company on the implementation plan based on their needs. This research will answer those research questions by referencing to the knowledge management theories on the People, Process, and Technology (PPT) as well as adopting Nonaka’s SECI model in knowledge transformation cycle and Jann model knowledge management framework (Jann). Since this research is the first stage of implementing knowledge management system, it will be a qualitative method used with data collection gathered through interviews. Data will be analyse using thematic analysis. There are several issues identified in relation of People, Process, and Technology. Ranging of the lack of professionalism, incomplete SOP, awareness and training program, and the minimum technology that is supporting operation team causing the inability of easy access to knowledge. By applying and utilize PPT, SECI, and as well as Jann framework, author manage to compile and design knowledge management system that is best fit for the company. Identifying the challenges, addressing capability gaps on the organization as well as identification of organization critical knowledge to achieve the objectives of implementation. This will be compiled into a plan in designing knowledge management system. With the implementation of the system, it will result enhancement for operation team to increase their productivity, enhance decision-making process that will benefit the company in the future and raised their competitiveness with their competitors. The implementation plan will begin in February 2024, and it will cover three enablers of KM people, process, and technology. Strengthen the implementation the organization will also create KM steering committee that will oversee, review, and manages the initiatives. The committee will also do the evaluation on the system in making sure that it is stay updated, measuring the impact, and identify necessary changes.